Designing green libraries with new technology for enhanced access to information (2016)
In the world today the idea and conception of designing green libraries with the newest technology is gaining momentum and the drive is for institutions to adopt green library buildings, by greening existing library facilities, embracing environmentally sustainable and supportive practices within the library, and providing green library services with technology All these eventually aim to provide access to information (ATI) in the best way possible. The notable most important things for making healthy and efficient sustainable libraries are ecology, technology and economy. The main objectives of this paper are to analyze the importance of green libraries; to identify the standards for green libraries with new technology; to identify the significant green library initiatives at various places; to reveal various methods and techniques for greening the library; and to make suggestions for building green libraries with new technologies for sustainable development and growth for enhanced ATI. The paper concludes that librarians have to work on updating themselves on sustainability and technology trends in the field of librarianship and should lay out awareness raising programmes and also design the space in the libraries with adequate consideration for enhanced access to information that exemplify the green practices with new technologies.